IMPLEMENTASI HAK TENAGA KERJA WANITA TERHADAP USAHA MIKRO, KECIL DAN MENENGAH DI KECAMATAN SAIL KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Rosya Luni Syarli; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Each person is essentially required to meet the needs of primary and secondary. To meet their needs, then there must be an attempt is made by bekerja.Melihat circumstances of the country now, working at a large company does require skill labor is very competitive. So that not a few people who are less able to compete in the work in the company. For people who have financially above average many are making a body of Micro, Small, and Menengah.Berbicara about workers, job placement services implemented to the workers to obtain work according to his ability, and the employer may obtain manpower in accordance with needs. Therefore it is pointed out as the competence of each individual that covers aspects of knowledge, skills, and attitudes work in accordance with established standards including wages. The review is no exception for women workers. In Indonesia alone, the worker / laborer lady pretty much cover as workers in Small and Medium Enterprises. But not a few violations in labor practices involving the rights of women workers who should not contradict with the provisions of Law No. 13 Year 2003 on Manpower. Although power kerjawanita within the scope of SMEs experienced many violations committed by businesses, but not less than those who continued his work on the grounds that the difficulty of finding a job. Setting work hours stipulated in the Act is not implemented properly. Such as setting work hours under age for female employees private rights that regulate menstrual leave or maternity leave and many other abuses committed businesses that are not in line as defined in Article 76, 77 and 82 of Law No. 13 of 2003 on Labor. There are still many businesses that often overlook the private rights of female employees by not running the legislation properly. Given this thesis, for women workers who do not understand their rights as workers, are expected for the future is able to open up horizons about the rights that should be received. This type of research is a sociological research, because the authors of the study on the effectiveness of the laws in force. This research was conducted in SMEs in the District Sail Pekanbaru city, while the sample population is a whole party related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interviews, questionnaires and literature study. Keywords: Labor rights, women-Micro, Small and Medium Enterprises